ASEAN-5 Monetary Integration: a Case Study of Equity Markets - Chaiphat, Channarong (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2014)
Economic integration is a current worldwide trend. In particular, in 2015 under the ASEAN Economic Community the third stage of economic integration - a single common market of ASEAN countries - will officially be implemented. Factors of production, products, services and labor can freely be mobilized between the ASEAN member countries. Later, ASEAN should aim to reach the higher stage of economic integration, which is monetary integration. It will be a key to link international business transactions and to support integration of economic real sectors to become more successful. According to the optimum currency area theory, it is indicated that countries sharing a single currency must have compatible economic variables. This article aims to examine the synchronicity of financial variables in ASEAN-5 by using equity market indices collected during the period from January 2003 to June 2013. Using the Cointegration test to analyze the data, the results reveal 8 pairs (out of 10 pairs) of cointegration relationships among ASEAN-5 markets indices, which include the markets of Malaysia and Indonesia, the Philippines and Indonesia, the Philippines and Malaysia, Singapore and Indonesia, Singapore and Malaysia, Singapore and the Philippines, Thailand and Malaysia, and Thailand and the Philippines. The results of analyzing for error correction mechanism show that when there are deviations from equilibrium, the eight pairs of ASEAN market indices will adjust to the long-run equilibrium with a positive relationship. As for the Thailand-Indonesia and Thailand-Singapore market indices, no long-run equilibrium is found. This study shows that most of the variables in equity markets of ASEAN-5 are symmetric and this will support the monetary integration of ASEAN-5 in the future.